Project Activities of Students as a Form of Developmental Teaching - Lazarev V. S (Moscow State University of Psychology and Education, 2015)
Project activities of students regarded as a form of developmental teaching. Coping with domestic school crisis is possible using the activity-related forms of education. Author believes that initiating of students project activities widely used in the practice of the last decade should be assessed positively. In most cases, what is presented as "project activity", in fact is not. Project activity contains significant opportunities for the realization of the idea of developmental education developed in the scientific school of cultural-historical psychology. Hypothesizing and experimental confirmation of the leading role of education in the development of the human mentality and working out the theory of developmental education are the biggest achievements of the scientific school. The theory of developmental education determines the educational activity in primary school and poorly designed for its middle and senior levels. It has inner problems that need to solve for further progress in building a new practice of schooling. It is shown how using the features of project activities can expand the boundaries of the implementation of the developmental education ideas